Investigations into high resolution imaging of the aqueous outflow system and cornea - Hong, Jesmond Xun Jie (Nanyang Technological University, 2018)
Advance imaging modalities are necessary for the accurate and early detection of glaucoma and corneal diseases. It enables vision researchers and clinicians to understand the disease state fundamentals and pathology, which are critical for follow-up and subsequent treatment. Timely and definitive diagnosis of ocular diseases, coupled with the mobilization of public health resources to create an increase in awareness for its prevention through innovative programs, is believed to have a positive impact on the global burden of visual disability. This is especially true in the case of glaucoma, where the aim of the treatment is to preserve the remaining vision. This thesis in this context aims to investigate the potential of Bessel beam and light sheet fluorescence microscopy for ocular disease diagnosis. The main objectives of this thesis are hence directed towards the research and development of novel concepts and methodologies using Bessel beam microscopy and light sheet fluorescence microscopy for high resolution diagnostic monitoring of open and close angle in glaucoma patients. With innovative optical engineering of the light sheet configuration, the illumination arm can be used for high resolution imaging and characterization of cornea. A flexible ocular imaging probe to record, capture, and display images of the iridocorneal angle region and fundus is also looked into. A flexible ocular imaging probe with uniform near field irradiance is conceptualized and developed based on a geometric model that simplifies the complex non-rotational symmetric irradiance distribution of light emitting diodes tilted at an angle. The imaging probe is an assembly of a circular ring array of four light emitting diodes tilted at an angle and a micro color charged coupled device camera. Its distal end is optimized and custom fabricated, following a theoretical analysis and modelling of the design parameters. It can be used to image critical anatomical structures of the aqueous outflow system and fundus. The imaging probe has resolutions of 10.08 line pairs per mm (~49.61 µm) at the iridocorneal angle region and 5.04 line pairs per mm (~99.21 µm) at the fundus. The use of near infrared sources for dark room provocation test enables a predictive and objective evaluation for detecting iridocorneal angle closure. The flexible ocular imaging probe can differentiate an open angle from a closed angle and note other pathological conditions, hence allowing proper classification and appropriate management. It has a better safety profile, is easier to implement, and reduces image acquisition time and patient discomfort as compared to conventional photographic methods such as gonioscopy and RetCam. A digitally scanned Bessel-Gauss light sheet fluorescence microscopy system to image the trabecular meshwork is proposed and developed. It is able to overcome the trade-off between the length and thickness of Gaussian light sheet to give better imaging performance. It has adequate spatial resolution to resolve the trabecular meshwork structures, thereby providing objective information about the aqueous outflow system and critical anatomical structures inside the eye. The higher axial resolution of this prototype is due to the thinner light sheet, and the ability of the Bessel-Gauss beam to reconstruct through scattering media. Images acquired are in sharp focus since the light sheet is thinner than the depth of field of the detection objective. The unique ability of the Bessel-Gauss beam to reconstruct itself also increases the image contrast at the trabecular meshwork, and minimizes the scattering and shadowing artifacts. The use of fluorescein sodium as a contrast agent further increases the anatomical discrimination and image contrast in the optical sections. The digitally scanned Bessel-Gauss light sheet fluorescence microscopy system has cellular/ subcellular spatial resolution, good optical sectioning, high imaging speed, and low photobleaching and photodamage. An indirect axicon assisted gonioscopy imaging system is also proposed and developed by integrating the concept of Bessel beam microscopy with conventional gonioscopy imaging. The proposed system can image with a spatial resolution of 3 µm and can reveal critical details of the trabecular meshwork. It is expected to aid the management of glaucoma by providing information complementary to angle photography and gonioscopy. Assessment and evaluation of trabecular meshwork pigmentation is critical in many protocols and grading techniques for glaucoma. Theoretical modelling, simulations, and experimental studies were performed for both configurations. Further, a methodology and integrated apparatus for the sequential imaging of the cornea and aqueous outflow system is configured, based on a Gaussian beam epi-illumination configuration and a Bessel-Gauss beam plane illumination configuration, respectively. The cornea imaging module has a spatial resolution of ~2.19 µm and can be used for high resolution imaging and characterization of cornea. Corneal topography is achieved by moving the scanning spot across eye in a raster fashion. The ability of the proposed configuration to provide cellular level resolution potentially enables identification and characterization of infectious agent during an inflammatory response. Vision researchers and clinicians can therefore classify the disease states without the need to mechanically remove samples from the cornea. The clinical significance of the proposed study is validated by performing imaging of the New Zealand white rabbit’s cornea infected with Pseudomonas. It is envisaged that the original contributions and major findings of this thesis can contribute towards the diagnosis, prognosis, and management of glaucoma and corneal diseases.